Equine laminitis: Bites by Bothrops spp cause hoof lamellar pathology in the contralateral as well as in the bitten limb - Acosta, Ofelia Cristina (2006)
The envenoming caused by Bothrops snakebite includes local symptoms, such as pronounced edema, hemorrhage, intense pain, vesicles, blisters and myonecrosis. The principal systemic symptom consists in the alteration of blood clotting, due to ﬁbrinogen consumption and platelet abnormalities. The horses involved in this study had this symptomatology and one of them exhibited symptoms consistent with laminitis in the bitten and in the contralateral limbs. Laminitis lesions were characterized by separation of the hoof lamellar basement membrane (BM) from basal cells of the epidermis. These results demonstrated that Bothrops snake venom can induce acute laminitis. We conclude that components of the venom, probably metalloproteinases, cause severe lesions in the hoof early in the envenoming process. Antivenom therapy must be initiated as soon as possible in order to prevent complications, not only to save the life of an envenomed horse, but also to avoid the dysfunctional sequels of laminitis.